1992
DOI: 10.1007/bf02298027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pollutants on sensory systems and behaviour of aquatic animals

Abstract: A wide variety of pollutants (for example, heavy metals, organic compounds such as pesticides, hydrocarbons and oil dispersants, radioactive materials, excessive nutrients, acids, litter, silt, temperature and explosions) can influence the function of sense organs, and so influence behaviour by reducing or changing sensory information reaching the brain. Experiments show that so-called sublethal effects of pollutants occur at much lower concentration thresholds than lethal effects, yet subethal effects may wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 84 publications
1
25
0
Order By: Relevance
“…Lacroix and Townsend (1987) have shown that pH alone can be responsible for severe ionic imbalance, leading to mortality of the fish, and that ionic depletion was further enhanced by Al (in combination with low pH). Besides mortality, metals and acidity also produce numerous sublethal effects, such as feeding impairment and other behavioral alterations (Lacroix and Townsend, 1987;Blaxter and Hallers-Tjabbes, 1992;Peakall, 1992;Heath, 1995;Gerhardt, 1998;Beaumont et al, 2000). Biomarker alterations are also among the sublethal outcomes caused by metals.…”
Section: Short-term In Situ Bioassay With Adult Fishmentioning
confidence: 97%
“…Lacroix and Townsend (1987) have shown that pH alone can be responsible for severe ionic imbalance, leading to mortality of the fish, and that ionic depletion was further enhanced by Al (in combination with low pH). Besides mortality, metals and acidity also produce numerous sublethal effects, such as feeding impairment and other behavioral alterations (Lacroix and Townsend, 1987;Blaxter and Hallers-Tjabbes, 1992;Peakall, 1992;Heath, 1995;Gerhardt, 1998;Beaumont et al, 2000). Biomarker alterations are also among the sublethal outcomes caused by metals.…”
Section: Short-term In Situ Bioassay With Adult Fishmentioning
confidence: 97%
“…The response of the effectors is then influenced with potential consequences on behavioral performance. In both fish and invertebrates, different sensory systems may be affected by contaminants such as light receptors, mechanoreceptors, chemoreceptors (Blaxter and Hallers-Tjabbes 1992;Scott and Sloman 2004). In aquatic biota, chemoreception is particularly important (Carreau and Pyle 2005).…”
Section: Relationship Between Behavior and Biochemical And Physiologimentioning
confidence: 99%
“…Overall, this is a quite relevant scientific issue since most species of fish depends greatly on vision as a source of information. The vision mediates a large range of fish behaviours, from feeding to orientation and schooling [Blaxter and Hallers-Tjabbes, 1992]. Thus, functional disruption of fish eyes due to Hg accumulation could influence fish fitness and survival by reducing or changing the sensory information reaching the brain.…”
Section: Introductionmentioning
confidence: 99%